Koncepcja umiejscowienia controllingu w strukturze Górskiego Ochotniczego Pogotowia Ratunkowego - Bielecki, Krzysztof (Conception of Location of Controlling in the Structure of Mountain Rescue Service, 2007)
Controlling in the activity of GOPR (Mountain Rescue Service) can be higly significant not only in turns of the rationalization of using resources needed for the mountain rescuing but also to optimalize the effects in relation to costs. Completely other role of controlling is creating procedures of insuring the rescuing activity and functioning of the organization in the arrangement of lack of financing this activity from the national budget in relation to loosing financing support from GOPR sponsors i.e. changes of economical situation on markets in the area of the GOPR main donors. Well functioning controlling system oriented at future, based on current occurrences and scenario analysis can become a serious tool in minimalizing the risk of financial insuring of activity and functioning of the organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 32-37